Effect of Extracted Walnut Pomace Cake Edible Coating and Packaging Type on Quality Parameters of Walnut (Juglans regia L.) Kernels During Long Storage Periods - Pradeep Kumar; Lilla Szalóki-Dorkó; Beatrix Szabó-Nótin; Julianna Kereszturi; Judit Tormási; László Abrankó; István Dalmadi; Dóra Székely; Mónika Máté (Applied Sciences, 2024)
Walnuts are highly valued for their rich nutritional content, but their quality degrades during storage due to oxidation and other quality reducing processes. This study investigated the use of bioactive compounds extracted from walnut pomace, a by-product of walnut oil production, to develop an edible coating that extends the shelf life of ‘Milotai 10’ walnut kernels. Walnut kernels were stored for eight months in four different packaging materials (PE, PP, MPP, PLA) and three treatments were used (air or without treatment, nitrogen gas, and walnut pomace extract coating). The effects of these combinations on walnut quality parameters, including polyphenol content, vitamin E, fatty acids, peroxide value, and color, were analyzed. The results show that the combination of metallized polypropylene packaging under nitrogen treatment or with atmospheric air and walnut pomace extract (MPP-A-E+) best preserves walnut quality, making it a promising option for extending shelf-life.